2017
DOI: 10.1002/ece3.3508
|View full text |Cite
|
Sign up to set email alerts
|

Eggshells as hosts of bacterial communities: An experimental test of the antimicrobial egg coloration hypothesis

Abstract: Oviparous animals have evolved multiple defenses to prevent microbes from penetrating their eggs and causing embryo mortality. In birds, egg constituents such as lysozyme and antibodies defend against microbial infestation, but eggshell pigments might also impact survival of bacteria. If so, microbes could exert an important selective pressure on the evolution of eggshell coloration. In a previous lab experiment, eggshell protoporphyrin caused drastic mortality in cultures of Gram positive, but not Gram negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 41 publications
0
4
2
Order By: Relevance
“…Also, Leleu et al [54] found a large variation in cuticle coverage and quality within groups of white and brown eggs from old hens, and Ishikawa et al [55] demonstrated that brown eggshells and their pigments were active against Gram-positive bacteria but not against Gram-negative bacteria including Salmonella Enteritidis. However, these results were not corroborated by Dearborn et al [56], where the proportion of Gram-positive bacteria on eggshells did not vary by egg color.…”
Section: Discussioncontrasting
confidence: 77%
“…Also, Leleu et al [54] found a large variation in cuticle coverage and quality within groups of white and brown eggs from old hens, and Ishikawa et al [55] demonstrated that brown eggshells and their pigments were active against Gram-positive bacteria but not against Gram-negative bacteria including Salmonella Enteritidis. However, these results were not corroborated by Dearborn et al [56], where the proportion of Gram-positive bacteria on eggshells did not vary by egg color.…”
Section: Discussioncontrasting
confidence: 77%
“…For example, it is possible that eggshell pigments modify the amount and wavelength of light transmitted through the eggshell and thus affect embryonic development (Maurer et al 2015, Lahti andArdia 2016). Eggshell pigments may play a thermoregulatory role (Bakken et al 1978, Westmoreland et al 2007, and pigments may also decrease trans-shell contamination by microbes (Ishikawa et al 2010, but see Fargallo et al 2014, Dearborn et al 2017. It is also possible that eggshell pigments strengthen thin eggshells (Gosler et al 2005, García-Navas et al 2010, Hargitai et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…For example, establishing some bacteria (e.g., Enterobacteriaceae ) on the eggshells of lizard ( Sceloporus virgatus ) can improve egg hatching success by protecting the embryos from fungal infection ( Bunker et al, 2021 ). In these respects, we speculate that the eggshell acts as a transgenerational carrier for symbiotic microbes ( Dearborn et al, 2017 ; van Veelen et al, 2018 ). In oviparous birds, symbiotic microbes are transmitted from mother to eggshell via brood patches, nest material, and maternal skin, but not the maternal cloaca ( van Veelen et al, 2018 ).…”
Section: Introductionmentioning
confidence: 98%